E-COMMERCE. ONLINE-SHOP: ITS DEVELOPMENT, IMPLEMENTATION STAGES, AND PROTECTION METHODS - TALANCHUK, DMYTRO; KRAVETS, RUSLAN (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article explores the problems of the functioning of e-commerce in Ukraine and a separate means of its management - an online store. The processes of the development of an online store are analyzed and investigated. The main stages of its implementation and the means of protecting the online store from external threats are described.Many companies that sell products create websites to increase profits. Creating a website requires relevant knowledge in this area. To increase profits, just creating a website will not be enough, you need to skillfully approach the development strategy and its design. The article describes the main stages of creating a site for a building materials store. Information models for a better understanding of processes are presented. The choice of CMS and its advantages are described, among which there are built-in payment systems and methods of delivery of goods. Describes the process of placing an order and the situation when the product is not. The process of the order confirmation is described. The information on what needs to be sent to the buyer after the order has been made and confirmed is described.The material presented in the article will help to find the right approach to creating and conducting online commerce. The article highlights the main aspects to consider when creating a website for sales. The material will help you choose a convenient CMS and provide information on the security of the website. The article will be useful to anyone who plans to open their website. Having a website in the company significantly enhances its image and has a positive effect on revenue, because then the company's services will be available to a large number of people. The article also addresses the security of the website to prevent hacking.
Keywords: business; information; Information Technology; e-commerce; content management system; online-shop; Internet